Preparation of Cellulose Graft Copolymer Based on Combination of Ionic Liquids and Microwave Heating - Liu, Dan-Hui; Luo, Wei; Wei, Yu-Zhen; Lin, Chun-Xiang; Du, Chao-Yang; Liu, Ming-Hua (Asian Journal of Chemistry, 2014)
Cellulose is a promising raw materials available and can be modified through a variety of chemical modifications to obtain functional materials. Cellulose-g-acrylamide copolymer was prepared in a homogeneous medium by using N,N’-methylenebisacrylamide as crosslinker without any radical initiator under microwave radiation. 1-Butyl-3-methylinidazolium chloride an ([Bmim]Cl) ionic liquid is an environment friendly and effective reaction medium, was chosen to dissolve cellulose and the homogeneous graft polymerization of acrylamide onto cellulose. Due to the effect of microwave heating, the reaction time was significantly shorten: 1 min microwave heating was adequate, compared with 0.5-5.0 h, as conventional heating was used. The influences of monomer concentration, crosslilnker dosage, microwave power and reaction time were investigated the obtained cellulose graft copolymer was characterized by IR spectrum, TGA and SEM. A feasible reaction mechanism of grafting based on microwave heating was put forward.